“Qui sont-je?” Multilingual Entanglements in Üstün Bilgen-Reinart’s Porcelain Moon and Pomegranates: A Woman’s Trek through Turkey - Karpinski, Eva (TTR)

(untitled) (Association canadienne de traductologie, 2018)
Hélène Cixous’s question “Who are I?” sets up the scene of this inquiry into the Turkish-Canadian writer Üstün Bilgen-Reinart’s plural self-translations at the crossroads of different cultures she has traversed during her life trajectory from Turkey to Canada and back to Turkey. I read her hybrid translingual family memoir-travel narrative for evidence of productive potentialities of multilingualism in cross-cultural encounters. Woven into the text are complex multilingual entanglements of her many languages, histories, and geographies, as she passes from Turkish to English and French while immersing herself in the stories told in Dene, the language of the Sayisi Dene in northern Manitoba, and collects Kurdish stories from southeastern Anatolia, translated into Turkish. In 1997, with Ila Bussidor, Üstün Bilgen-Reinart co-authored Night Spirits, an oral history of the forcible relocation and subsequent rebuilding of the Sayisi Dene community. Bilgen-Reinart’s perception of the present-day situation in Turkey, after her thirty-year stay in Canada where she worked as a CBC journalist, is influenced by Indigenous knowledges that she has been exposed to and by her transnational feminist consciousness. Her life writing affords a unique possibility for exploring the intersections of migrant, diasporic, and Indigenous histories through affective theorizing of the wounds of trauma, displacement, and dispossession. Constructing the “I”-witness position vis-à-vis the disastrous social, political, cultural, and ecological consequences of colonialism and globalization, her text explores relational linkages that extend beyond the singular self and create connections between multiple bodies, lives, and their environments. Her practice of drawing complex webs of meaning can be read in terms of decolonial multilingual languaging.